Stanislav Voronin’s Universal Classification of Onomatopoeic Words: a Critical Approach (Part 2) - M. A. Flaksman (Дискурс, 2021)
Introduction. The present paper is a critical study of the classification methodology introduced by S. V. Voronin in 1969. The phonosemantic classification of onomatopoeic (sound imitative) words has been tested on the material of typologically different languages and, in general, has proven itself successful. However, the bulk of empirical evidence calls for minor updates on the classification. The first part of the article contained a detailed description of the classification and a critical analysis of its various aspects. This (the second) part contains suggestions as how to overcome the highlighted difficulties.Methodology and sources. The method applied in the classification is the method of phonosemantic analysis which was introduced by S. V. Voronin. The present article explores the possibilities of its application on data from English and other relevant languages.Results and discussion. The critical analysis of the universal classification of the onomatopoeic words conducted in the first part of the article revealed the presence of several overlapping classes and hyperclasses, as well as other minor inconsistencies. The introduction of additional hyper-classes and re-classification of frequentatives helps to overcome these difficulties. Thus, I move frequentatives-instants and frequentatives-continuants from the class “frequentatives” to form a hyper-class of their own, leaving what were Voronin’s “pure” frequentatives in the former class of frequentatives. I also introduce poly-syllabic onomatopoeic words into the classification.Conclusion. The introduced changes do not not undermine the key principles of the Universal classification formulated by S. V. Voronin but help its practical implementation on the material of typologically different languages.